The patriarchal family’s relation with tyranny at Abu Ali Yassin - علاء الدين غسان; حيدر يارا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research tries to identify the most important ideas that are presented by Abu Ali Yassin during his talk about the close relationship between the patriarchal family (patriarchy) and the production of tyranny in the Arab world and the consequent creation of cowardly, obedient generations that are subject to any irrational, tyrannical authority because they are basically addicted to obedience and submission. And I was brought up on them, and therefore we must reconsider the values and ideas produced under the shadow of this patriarchal family and replace them with the values of liberation and independence that the Arab world will not have a civilized status among nations in their absence